ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH - Ramdany Ramdany; Yusuf Setiawan (STIE Muhammadiyah Jakarta, 2021)
The study aims to determine the effect of the Agency Level Financial Application System (SAKTI), the competence of Human Resources (SDM), Internal Control (PI) on the Quality of Government Financial Reports (KLKP). This study uses a quantitative approach. Data was collected through questionnaires from 92 respondents to the SAKTI application operator at the Directorate General of Treasury's work unit, Ministry of Finance. Data analysis using SmartPLS. The results showed that the implementation of SAKTI and PI had a significant effect on KLKP, while SDM competencies had no effect on KLKP. This research is limited to conduct within the work unit of the Directorate General of Treasury on the island of Java.